A Facile, Template‐Free Synthesis of AgCl Hierarchical Architectures: Precursors of Highly Efficient Visible‐Light Plasmonic Photocatalysts of Ag@AgCl. Issue 4 (3rd March 2014) - Wang, Yu; Chen, Gang; Di, Andi; Xu, Haiming
Abstract This paper describes a facile, template‐free synthesis of AgCl hierarchical structures by a gas–liquid interfacial method and the morphology of AgCl (microrods or film) can be conveniently varied or controlled by changing the solvents of AgNO3 without using any surfactants. The AgCl composites were then photoreduced to form highly efficient visible‐light plasmonic photocatalyst Ag@AgCl nanostructures. SEM, XRD, X‐ray photoelectron spectroscopy, and UV/Vis diffuse reflectance spectroscopy were used to characterize the obtained product. The photocatalytic activity of the obtained product was evaluated by the photodegradation of methyl orange pollutant under visible‐light irradiation, and it was found that Ag@AgCl microrods exhibited high visible‐light photocatalytic activity and good stability.